Verification of the three-dimensional structure of synthesized molecule by molecular dynamic simulations - Bigovic, Miljan; Zecevic, Zarko; Filipovic, Luka; Krstajic, Bozo (IEEE EUROCON 2017 -17th International Conference on Smart Technologies, 2017)
The paper presents comparison between molecular models made by using software packages, experimental results and performed simulations in molecular dynamics area with created molecule. Molecule was synthetized using organic synthesis strategy. After structural analysis, precise layout of all the atoms in space was determined. Molecule was converted into standard chemical format, visualized and prepared for simulations. Here we intend to show that it is possible, by using powerful computer infrastructure and related applications, to create good models of molecules, which can be used in simulations that produce valid characteristics of subject molecules interacting with various organic compounds.